Evaluating the toxic efficacy of some bio-insecticides against mature stages of whitefly insect (Bemisia tabaci). - Alyaa abdul-ridha hanash (Wasit Journal for Pure Sciences, 2023)
This work was conducted to assess the effectiveness of three bio- insecticides (Spinosad, Abamectin and Thiomethoxam) against the mature stages of the whitefly (Bemisa tabaci): Aleyrodidera. HomoPtera . The results showed all pesticides it was active in decreasing the population density of adults in first day after spraying, after which its effectiveness it started to decrease after the 3rd and 7th day of spraying, on the other hand, the lowest population density of nymphs was recorded from day 7 onwards after 2nd spray with pesticides. 17.42 adults/10 leaves and 9.82 nymphs/16 cm2 was the lowest population density after 2nd spray of pesticides comparison with the durations before spraying and the 1st spray, which reached rate of population density (55.14 and 25.37) adults 10/leaf and (47.93 and 21.8) nymphs 16/cm2 respectively, Spinosad pesticides were characterized reduced the population density of adult after (1 and 3) days for each of the 1st spray, which reached an average of (2.11, 3.77) insects/10 leaf and (1.66, 2.66) insects/10 leaf for the 2nd  spray respectively and for the nymphs at the 2nd  spray after (1, 3, and 7) days, which reached an average of (8.66, 4.88, 3.88) nymph/16 cm2 respectively . The present results it shows the effectiveness of the biological agents used (bio-pesticide) and demonstrate that biological insecticides can be used in the management of whitefly by following safety instructions for the use of insecticides and choosing the right time to harvest the plants this is to avoid harm from pesticides as much as possible.